RELIABILITY, RESPONSIVENESS, DAN EMPHATY TERHADAP KEPUASAN KONSUMEN MALL PELAYANAN PUBLIK DI KABUPATEN SUMENEP - Wijaya, Nur Qoudri; Ghufrony, Ahmad; -, Raudatunnisah (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2021)
The problem examined in this thesis is that there are problems that need to be repaired and improved such as the building used does not cover the number of companies in it so that on certain days many consumers still lack seats in the waiting room, as for another thing, the parking spae provided is not very wide so disturbing the public facilities in the parking area of the town square of Sumenep. Therefore, to find out more about the service quality of public service Malls in Sumenep district, the researchers conducted research with the title of service quality (Reliability (X1), Responsiveness (X2), and Emphaty (X3) ) on consumer satisfaction in Public Service Mall in Sumenep Regency. In answering these problems, researches used purposive sampling method, namely the method of determining the sample with certain considerations. The results of the researcher show that the variables of Reliability (X1), Responsiveness (X2), and Emphaty (X3) have a significant effect on customer satisfaction in order to improve the quality of service and the comfort of the community while at the Public service Mall in Sumenep Regency.